Changing the Waveform of Circadian Rhythms: Considerations for Shift-Work - Harrison, Elizabeth M.; Gorman, Michael R. (Frontiers in Neurology, 2012)
Circadian disruption in shift-work is common and has deleterious effects on health and performance. Current efforts to mitigate these harms reasonably focus on the phase of the circadian pacemaker, which unfortunately in humans, shifts slowly and often incompletely. Temporal reorganization of rhythmic waveform (i.e. the shape of its 24 h oscillation), rather than phase, however, may better match performance demands of shift-workers and can be quickly and feasibly implemented in animals. In fact, a bifurcated pacemaker waveform may permit stable entrainment of a bimodal sleep/wake rhythm promoting alertness in both night and daylight hours. Although bifurcation has yet to be formally assessed in humans, evidence of conserved properties of circadian organization and plasticity predict its occurrence: humans respond to conventional manipulations of waveform (e.g., photoperiodism); behaviorally, the sleep/wake rhythm is adaptable; and finally, the human circadian system likely derives from the same multiple cellular oscillators that permit waveform flexibility in the rodent pacemaker. In short, investigation into untried manipulations of waveform in humans to facilitate adjustment to challenging schedules is justified.